Informal economic education on construction porters families - Dharma, Dwiasa Sambhawa; Amalina, Endah Nur (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2024)
The research that has been conducted is intended to explore in-depth informal economic education for families of construction porter workers in Ngadirenggo Village, Blitar Regency.  A phenomenological approach in the qualitative method is used to examine the problem. In this study, six construction porter workers in Ngadirenggo Village became informants and subjects. The data analyzed is in the form of primary and secondary data. The results show that:  (1) the economy of the building Construction porters family in Ngadirenggo Village is sufficient in meeting primary needs, (2)  the values of economic education instilled in children in the form of money management, the importance of saving and saving attitudes and behaviors, the introduction of parental work, (3) the impact of informal economic education on building Construction porters families is seen in    Children's behavior and attitudes in saving, saving,  and consuming and become accustomed to economic activities and are more independent.   Based on these results, parents in informal economic education must maintain communication and provide examples so that the learning atmosphere of managing money is shady comfort in the family can be created and give meaningful meaning to the child's life in the future.